From Paper to web: Students as partners for virtual laboratories in (Bio)chemical engineering education - Caño de las Heras, Simoneta; Gargalo, Carina L.; Caccavale, Fiammetta; Kensington-Miller, Barbara; Gernaey, Krist V.; Baroutian, Saeid; Krühne, Ulrich (Frontiers in Chemical Engineering, 2022)
The integration of online platforms in education has increasingly become a matter of fact at all educational levels. Examples such as virtual laboratories in tertiary education have shown their benefits, such as the decreased cost and resources needed as well as providing a safer environment for practical experimentation. However, students or stakeholders are not usually involved in developing the virtual laboratory, even if, when given the opportunity, they can provide valuable feedback for improvement and acquire ownership over the platform. Hence, when proposing a novel educational process virtual laboratory that targets teaching bioprocess modeling to undergraduate students, the best approach is to involve the students in the development as its future users. To this end, in this work, four co-participatory design experiences are presented that show the journey from a paper prototype to an online educational virtual laboratory (www.biovl.com). Qualitative and quantitative data have been collected in two different universities through surveys, semi-structured interviews, and informal conversations among the students and the developer. The students’ perspectives were found to provide valuable feedback about the platform’s content, usability, and functionality. For example, interest in adding bioprocess-related coding activities, or suggesting changing the platform name, were opinions collected and carefully considered. These suggestions can be easily integrated since the software is at the early stages of the virtual laboratory prototype. Although the usability and functionality features of the platform are under continuous advancement, this work’s findings show that the students are interested in contributing to the virtual laboratory’s development. Therefore, it opens the door to modifications and improvements, which are strongly based on the users’/students’ perceptions and perspectives as the virtual laboratory’s co-designers. Furthermore, the educational strategy proposed in this work can be replicated by those who want to develop other virtual laboratories.